Obtenção de nanopartículas coloidais de trifluoreto de itérbio - Silva, Patricia Batista Teixeira da (2011)
Radiopaque dental composites are materials that have attracted great scientific and technological interest due to their different optical and mechanical properties when compared to polymer-based dental materials. In this work, dental resin nanocomposites were prepared with the assynthesized YbF3 nanoparticles by mixing the components in the colloidal state. YbF3 nanoparticles were synthesized by hydrothermal processing. In this method, it was added an aqueous solution containing YbCl3 and Na3C6H5O7.2H2O. Additionally, NH4F and NaBF4 were used as fluoride source. Resulting in nanoparticles with average size around 10 nm, which consisted of orthorhombic phase. In addition, nanocomposites were prepared with the dental resin YbF3 obtained. Which showed higher radiopacity than the tooth tissue with 20% in weight (w/w) using the as-synthesized YbF3 nanoparticles.